EXPERIMENTAL STAPHYLOCOCCUS AUREUS INFECTION OF THE MAMMARY GLAND INDUCES REGION-SPECIFIC CHANGES IN INNATE IMMUNE GENE EXPRESSION - WHELEHAN, CORMAC; O'FARRELLY, CLIONA (Elsevier, 2011)
Staphylococcus aureus is a prolific mastitis-causing bacterium that resides naturally in the environment of the dairy cow. The aim of this study was to profile immune gene expression in tissue from the alveolar, ductal, gland cistern and teat canal regions of the bovine mammary gland following intra-mammary infection with S. aureus. Quantitative real-time PCR (qPCR) was used to profile expression of innate immune genes including pattern recognition receptors (PRRs), cytokines, chemokine, antimicrobial peptides (AMPs) and acute phase proteins (APPs). Consistent expression of Toll-like receptors (TLRs) 1-10 and NOD-like receptors (NODs) 1-2 was detected in all four tissue regions. Pro-inflammatory cytokines (IL6, IL17A and IL8) and anti-inflammatory cytokine (IL10) were induced in all 4 tissues. APP (SAA3 and HP) and AMP (DEFB4 and DEFB5) genes showed the greatest induction throughout the mammary gland in response to S. aureus, with particularly high expression in alveolar tissue (SAA3 and HP >133- and >80-fold respectively, P <0.05; DEFB4 and DEFB5 >9- and >27-fold respectively, P <0.05). Collectively, our data show both sentinel and effector immune functions throughout the mammary gland in response to S. aureus challenge.
PUBLISHED
Keywords: Immunology; Staphylococcus aureus